2015
DOI: 10.1155/2015/901046
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral Risk-Reducing Mastectomy: Review of Risk Factors and Risk-Reducing Strategies

Abstract: Rates of contralateral risk-reducing mastectomy have increased substantially over the last decade. Surgical oncologists are often in the frontline, dealing with requests for this procedure. This paper reviews the current evidence base regarding contralateral breast cancer, assesses the various risk-reducing strategies, and evaluates the cost-effectiveness of contralateral risk-reducing mastectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 59 publications
0
23
0
1
Order By: Relevance
“…Overall uptake of contralateral riskreducing mastectomy was 14 % over a 25-year periodhowever the rates are increasing rapidly with the passage of time-10 % (1985-2001) -22 % (2001-2010). SEER (Surveillance, Epidemiology and End Results Program) data indicate a 150 % increase in the rates of contralateral risk-reducing mastectomy that includes mutation carriers and non-BRCA1/2 high family risk patients [7]. Rhiem et al [26] found that the risk of contralateral breast cancer for BRCA1/2 negative families is low and similar to that in women with sporadic breast cancer, confirming our finding that contralateral breast cancer risk is dependant on mutation status and age of onset of first breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall uptake of contralateral riskreducing mastectomy was 14 % over a 25-year periodhowever the rates are increasing rapidly with the passage of time-10 % (1985-2001) -22 % (2001-2010). SEER (Surveillance, Epidemiology and End Results Program) data indicate a 150 % increase in the rates of contralateral risk-reducing mastectomy that includes mutation carriers and non-BRCA1/2 high family risk patients [7]. Rhiem et al [26] found that the risk of contralateral breast cancer for BRCA1/2 negative families is low and similar to that in women with sporadic breast cancer, confirming our finding that contralateral breast cancer risk is dependant on mutation status and age of onset of first breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…During the extended observation period in our study, there have been inevitable changes in practice-one of the main being a global decrease in the incidence of contralateral breast cancer [7,27]. We have accounted for some of these potential confounding factors, particularly the omission of oestrogen receptor status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reviewed risk factors for CBC 15 and designed a questionnaire to assess some of these factors. In particular, we wanted to gauge how surgeons assess requests for CRRM, what factors they considered important when recommending this procedure and issues on funding.…”
Section: Methodsmentioning
confidence: 99%
“…Basu et al, summarized 15 the main factors increasing the risk of developing CBC which were listed as follows:…”
Section: The Perceived Risk Vs the Real Risk Of Cbcmentioning
confidence: 99%